Предмет: Химия,
автор: Rak2001
Осуществить превращения Fe->Fe2O3->FeCl3->Fe(OH)3->Fe2(SO4)3
Ответы
Автор ответа:
0
4Fe + 3O2 = 2Fe2O3
Fe2O3 + 6HCl = 2FeCl3 + H2O
FeCl3 + 3 NaOH = Fe(OH)3 + 3NaCl
2Fe(OH)3+ 3H2SO4 = Fe2(SO4)3 + 6H2O
Fe2O3 + 6HCl = 2FeCl3 + H2O
FeCl3 + 3 NaOH = Fe(OH)3 + 3NaCl
2Fe(OH)3+ 3H2SO4 = Fe2(SO4)3 + 6H2O
Похожие вопросы
Предмет: Математика,
автор: yalet53071
Предмет: Математика,
автор: angelinazoz555
Предмет: Английский язык,
автор: efremov1409
Предмет: Литература,
автор: НаталиБ1
Предмет: Математика,
автор: равиисмо